Characterizing the nature of worry in a sample of perinatal women with generalized anxiety disorder. (5th December 2019) - Goldfinger, Corrie; Green, Sheryl M.; Furtado, Melissa; McCabe, Randi E.
Abstract: Prevalence of perinatal anxiety disorders continues to grow, with estimates greater than those of postpartum depression. Generalized anxiety disorder (GAD) is the most commonly reported perinatal anxiety disorder, yet very little is known about the worry content experienced during the perinatal period in those with GAD. This study investigated worry content and frequency in a sample of perinatal women ( n = 20) and age‐matched nonperinatal women ( n = 20) diagnosed with GAD. Participants completed the Penn State Worry Questionnaire (PSWQ) to assess worry severity, in addition to providing their current top worries. Mean scores on the PSWQ in both samples exceeded a clinical cut‐off score of 65, and thematic analyses revealed that perinatal women experienced significantly greater parental‐themed worries compared with the nonperinatal GAD sample ( p < .05). Capturing the unique content of worry for perinatal woman will assist clinicians in identifying treatment targets and may enhance treatment outcome.